Ru-Mediated and Sulfur-Directed ortho-C–H Activation of Benzyl Thioethers with Internal Alkynes and Selective Hydrothiolation of Acetylene Dicarboxylates - Kumari, Sangeeta; Tomar, Vijesh; Soni, Aditi; Manisha, Manisha; Sharma, Charu; Joshi, Raj K. (Synthesis, 2024)
In this report, we have established a Ru(η6-C6H6)Cl2 catalysed ortho-C–H activation of benzyl thioethers with alkynes under milder reaction conditions. The sulfur atom of benzyl thioethers worked as a directing group for ortho-C–H activation of benzyl thioethers. The reaction was found to tolerate a range of benzyl thioethers as well as alkynes. Moreover, the reaction is significantly influenced by the length of alkyl and aryl thioethers, with the best results being obtained with benzyl thioethers. Kinetic isotopic experiments suggest that the ortho-C–H bond-breaking is not a rate-determining step for the present reaction. In an unusual observation that has not been reported, apart from ortho-C–H activation, under the same reaction conditions, a selective debenzylative hydrothiolation was exclusively obtained with acrylates, which broadens the synthetic impact of benzyl thioethers for the preparation of mixed chalcogen ethers.
Keywords: Ru-catalysis; sulfur directing groups; ortho-C–H activation; debenzylative hydrothiolation; thioethers